The Phenomenon Of Interactive Marketing Of "Skintific" Products Through Social Media And Influencers On Gen Z And Gen Y - Inka Sabila Juliamida; Andreans Bagaskhara; Mohamad Zein Saleh (OPTIMAL Jurnal Ekonomi dan Manajemen, 2024)
This journal aims to explain how interactive marketing through social media and influencers can increase brand awareness, consumer loyalty, and purchase decisions on Skintific generation Z and Y products. Qualitative research methods with a literature approach are used to explain the phenomenon of interactive marketing of Skintific products through social media and influencers in gen z and y with the deepest way of data collection, which shows the importance of depth and detail of these variables. The results showed that interactive marketing through social media and influencers had a positive impact on the purchasing decisions of Generation Z and Y towards Skintific products. This strategy not only increases brand awareness, but also strengthens consumer loyalty, making Skintific products in demand among the younger generation.